(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Among the various natural fibres, sisal is of particular interest in that its composites have high impact strength besides having moderate tensile and flexural properties compared to other lignocellulosic fibres. Investigations have been carried out in many countries on the various mechanical properties, physical performance and durability of cement based matrices reinforced with naturally occurring sisal fibres. The conventional concrete is strong in compression and weak in tension in order to overcome the steel reinforcement is being provided. The sisal fibre with the mechanical properties such as the compressive strength, modulus of rupture and split tensile strength of M40 grade concrete and by varying dosage of fibre content from 0, 1, 2, 3. The optimum dosage of sisal fibre was found to be 2.